Effect of Particle Flow Rates on Erosion Ratio in Particle Impingement Experiments. Issue 1 (January 2020) - Lin, Nan; He, Renyang; Zhang, Hao; Wang, Junqiang; Ma, Honglian; Huang, Hui
Abstract: Erosion caused by solid particles could not be neglected in oil and gas transportation industry, especially in gathering gas pipelines. Particles with small size may also erode the inner wall of pipelines after cumulative impacting and even lead to the leakage. Normally, a lot of solid particles are carried in the gathering gas before filtrating. Additionally, corrosion productions may fall off the wall as the gas flowing. Researches on erosion of pipeline caused by solid particles are important for predicting the remaining wall thickness, which can be a guide for pipeline inspection and safety protection. However, effect of particle flow rates on erosion ratio is normally omitted in studies on erosion ratio calculations. It was observed that particle flow rates have a great influence on the mass loss of specimens in the impingement experiments of this work. According to groups of Particle Tracking Velocimetry (PTV) results obtained under various conditions, the particle velocity decreased when the particle flow rate was larger under the same experimental condition and the mass loss of the specimen became lower. Relations between particle velocity and particle flow rate under different experimental conditions were calculated according to the PTV results. Further, relations between erosion ratio and particle flow rate were purposed in this work. It is better to consider effect of particle flow rate while calculating solid particle erosion of pipelines in industry.